PENDAMPINGAN MASYARAKAT DESA WISATA SANO NGGOANG SEBAGAI LANGKAH AWAL PENETAPAN DESTINASI WISATA SUPER PRIORITAS KOMODO- LABUAN BAJO - Yustus Sentus Halum; Ely Heldydiana Selamat; Fransiskus Jemadi; Siprianus Hame (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The Five Super-priority Tourist Destinations have been set by the Government of Indonesia in 2019. One of the selected tourist destinations is Komodo-Labuan Bajo. This determination of course affects many sectors and dimensions of people's lives; one of which is the readiness of tourist villages in the super destination area. The target of community service activities is the local population by involving their participation in the field of community improvement and empowerment. This participation is the first step for them to make changes in the tourism sector. Activities that have been carried out in this community service program include assistance in homestay business management, simple English language training, and ordering local tourism guides as an effort to sustain self-management participation based on existing local wisdom. As a first step, of course the sustainability of institutional networking activities is highly expected.